Meshless methods for modeling of laminated composite plates - Wang, Jin. (2008)
This thesis reports the applicability of the Reproducing Kernel Particle Method (RKPM) for the analysis of laminated composite plates. The work includes linear and nonlinear analysis of laminated composite plates by the presented RKPM approaches, incorporating first-order shear deformation plate theory (FSDT). The applicability of the RKPM is examined and extended by systematical studies for laminated composite plates. The enforcement of essential boundary conditions is a difficult task for the analysis of meshless approximations. Because the basic RKPM shape function does not possess Kronecker delta properties, usually some transformations are needed to obtain the nodal displacements or other quantities. In this thesis, the full transformation method and the singular kernel method have been used to enforce the boundary conditions. These two methods modify the RKPM shape function to satisfy the Kronecker delta properties; the boundary conditions can then be easily treated as in finite element analysis. The singular kernel method is the first application for RKPM analysis.